How English as first additional language is taught and used in quintile one primary school in Grade 4 where learners officially change from isiXhosa to English as the language of instruction: a case study - Marshall, Alexander Carlton (School of Education, 2015)
This study explores how learners in a township primary school learn, and are taught through the medium of English, in a community of pre-dominantly Xhosa speakers, and where English is seldom spoken or heard. The school is typical in the sense that learners from Grade 1 to Grade 3 are taught in isiXhosa as home language, with English as subject, after which they switch to English as the language of teaching and learning from Grade 4 onwards. The study concerns itself with the language and literacy practices at this pivotal switch-over point, and investigates to what extent learners in the Grade 4 English classes have learnt / been taught / have developed sufficient basic inter-personal communication skills, BICS, (Cummins, 1984), in English to make the switch to learning all subjects in English. The study also includes analysis of data gathered in two Natural Science lessons, in search of how the same Grade 4 learners learn, and are taught subject- specific knowledge in English. Classroom discourse patterns, which includes safetalk (Chick, 1996) and safetalk and safetime (Hornberger and Chick, 2001) and the kind of teaching practices prevalent in schools in post-colonial countries are examined to explain the low proficiency level of the typical Grade 4 learner at this critical point in English language learning.